## Calculus with Applications (10th Edition)

$\bar c{\,^,}\left( x \right) = \frac{{ - 3x - 4}}{{2{x^2}\sqrt {3x + 2} }}$
$\begin{gathered} c\,\left( x \right) = \sqrt {3x + 2} \hfill \\ The\,\,average\,\,cost\,\,is\,\,defined\,\,by \hfill \\ \bar c\,\left( x \right) = \frac{{c\,\left( x \right)}}{x} \hfill \\ \bar c\,\left( x \right) = \frac{{\sqrt {3x + 2} }}{x} \hfill \\ The\,\,marginal\,\,cost\,\,is\,\,given\,\,by \hfill \\ \frac{d}{{dx}}\,\,\left[ {\bar c\,\left( x \right)} \right] = {\left[ {\frac{{\sqrt {3x + 2} }}{x}} \right]^,} \hfill \\ Use\,\,the\,\,quotient\,\,rule \hfill \\ \bar c{\,^,}\left( x \right) = \frac{{x\,{{\left( {\sqrt {3x + 2} } \right)}^,} - \sqrt {3x + 2} \,{{\left( x \right)}^,}}}{{\,{{\left( x \right)}^2}}} \hfill \\ \bar c{\,^,}\left( x \right) = \frac{{x\,\left( {\frac{3}{{2\sqrt {3x + 2} }}} \right) - \sqrt {3x + 2} }}{{{x^2}}} \hfill \\ Simplifying \hfill \\ \bar c{\,^,}\left( x \right) = \frac{{3x - 2\,{{\left( {\sqrt {3x + 2} } \right)}^2}}}{{2{x^2}\sqrt {3x + 2} }} \hfill \\ \bar c{\,^,}\left( x \right) = \frac{{ - 3x - 4}}{{2{x^2}\sqrt {3x + 2} }} \hfill \\ \end{gathered}$